Mikroenkapsulasi Minyak Bandeng Omega-3 Melalui Wet Rendering dan Netralisasi Alkali Teroptimasi untuk Mutu Oksidatif - Fattah, Nurlaeli; Rahmawati Saleh; Ernawati Jassin; Imran Muhtar (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of fish oil as a natural source of omega-3 fatty acids, particularly EPA and DHA, often encounters challenges such as oxidative instability, unpleasant fishy odor, and variations in composition. This research focused on producing omega-3–enriched milkfish (Chanos chanos) oil that meets quality standards for microencapsulation, applying the wet rendering method followed by alkali neutralization with NaOH. The process involved varying temperatures of 70, 80, 90, and 100 °C and heating times of 30, 40, and 60 minutes. The crude oil obtained was refined using different NaOH concentrations, then evaluated for oxidative parameters including peroxide value (PV), p-anisidine value (p-AV), total oxidation value (TOTOX), and acidity levels (acid value/free fatty acids, FFA), all compared with International Fish Oil Standards (IFOS). The maximum yield recorded was 0.29% at 100 °C for 60 minutes. The results showed that PV and p-AV values were still within acceptable IFOS limits (3.44 meq/kg and 11.75 meq/kg), and TOTOX values remained below 20, indicating good oxidative stability. However, prolonged heating led to increased acid values/FFA ranging from 2.43% to 2.68%, surpassing IFOS limits and reflecting hydrolytic degradation of the oil. These findings demonstrate the trade-off between achieving higher yields under higher temperature and longer heating versus maintaining oil quality. Therefore, optimal processing at a maximum of 100 °C and not exceeding 30 minutes, combined with alkali neutralization, is recommended to ensure the production of stable, high-quality milkfish oil suitable for encapsulation and incorporation into health-oriented functional foods.